The Educational Role of BUMDes in Community-Based Tourism: Strengthening Local Cultural Identity and Social Innovation in Lombok’s Waterfall Tourism - Mulyana, Rizky; Maemunah, Maemunah; Isnaini, Isnaini (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the educational role of Village-Owned Enterprises (BUMDes) in supporting village tourism development, strengthening local cultural identity, and fostering social innovation through community-based learning processes in the waterfall tourism area of Senaru Village, North Lombok. Tourism development in this context is not only viewed as an economic activity but also as a medium for community education that promotes local knowledge, cultural values, and environmental awareness. A qualitative descriptive approach was employed to explore these phenomena in depth. Data were collected through direct observation, in-depth interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data collection, data reduction, data display, and conclusion drawing. The findings indicate that Senaru Village has strong potential for educational tourism derived from its natural attractions, such as Tiu Kelep and Sendang Gile waterfalls, traditional Bale houses, and the ancient Bayan Mosque, which function as spaces for cultural, historical, and environmental learning. BUMDes plays a strategic role in facilitating community education by empowering youth, women, micro and small enterprises, and traditional groups through participatory tourism management. The involvement of women through the Women Gaet organization as culturally knowledgeable tour guides reflects an informal educational process that enhances visitors’ learning experiences while simultaneously strengthening local capacity and social innovation. However, several challenges remain, including limited accessibility, environmental cleanliness, and visitor safety, which indicate the need for strengthened educational awareness and capacity building in sustainable tourism management. This study concludes that integrating education and local wisdom into village tourism development contributes to sustainable social, cultural, and economic development while reinforcing village identity and community resilience.